2017
DOI: 10.11604/pamj.2017.26.57.9021
|View full text |Cite
|
Sign up to set email alerts
|

Free-living amoebae isolated in the Central African Republic: epidemiological and molecular aspects

Abstract: Among the many species of free-living amoebae infecting humans, only Naegleria fowleri, a few species of Acanthamoeba, Balamuthia mandrillaris recently Sappinia diploïdea and Paravahlkampfia Francina are responsible for human diseases especially deadly encephalitis outside of Acanthamoeba keratitis related. In the Central African Republic (CAR), no studies have previously been conducted about free amoebae and no suspicious cases of encephalitis or amoebic keratitis was reported even though the ecosystem suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, our results are original for the three other soils. To our knowledge, Tetramitus is poorly studied in the literature and only one study showed that the predominant amoebal genus in the environment is Tetramitus (Farra et al 2017). Recently, a study on treated and untreated water samples showed that Naegleria was the major genus found in water samples (Majid et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are original for the three other soils. To our knowledge, Tetramitus is poorly studied in the literature and only one study showed that the predominant amoebal genus in the environment is Tetramitus (Farra et al 2017). Recently, a study on treated and untreated water samples showed that Naegleria was the major genus found in water samples (Majid et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These organisms play an important role in ecosystems, both as reducers and re-enders of bacterial biomass (Nagyová et al 2010, Vaerewijck et al 2014. Despite the large number of amoeba genera and species described in nature, only some species of the genus Acanthamoeba spp., and the species Naegleria fowleri and Balamuthia mandrillaris, are the ones that have the highest incidence in human infections (Marciano-Cabral et al 2003, Farra et al 2017, Javanmard et al 2017, Visvesvara et al 2007). Most FLA have two stages during their life cycle, the cyst form being the one that gives them great resistance to adverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(56,(108)(109)(110) Molecular investigations become a worthwhile approach to broaden the knowledge about FLA geographic distribution and have been used by the newest studies concerning pathogenic FLA to obtain a faster and more reliable detection of the aetiological agent in clinical samples. (70,(111)(112) Likewise, studies aiming at FLA environmental occurrence have combined the molecular strategies, with the morphological investigations. (113) Even though in the past 50 years, outbreaks have been related to PAM and GAE infections, (48,114) heightening the concern with water as an important path to new cases, FLA is considered as a neglected waterborne parasitic protozoan group.…”
Section: Clinical Importancementioning
confidence: 99%
“…3.48), critical areas were highlighted and may need continuous surveillance to pathogenic FLA presence as future risk management measures. As environmental amoebas infect the host by direct contact (111)(112) it is of great public health importance the knowledge of FLA occurrence, lightened up on the regional scale based on Monjolinho river (Fig. 3.…”
Section: 48)mentioning
confidence: 99%